Evaluation of a rapid antigen test (Panbio™ COVID-19 Ag rapid test device) for SARS-CoV-2 detection in asymptomatic close contacts of COVID-19 patients. (April 2021) - Torres, Ignacio; Poujois, Sandrine; Albert, Eliseo; Colomina, Javier; Navarro, David
Abstract: Objectives: There is limited information on the performance of rapid antigen detection (RAD) tests to identify SARS-CoV-2-infected asymptomatic individuals. In this field study, we evaluated the Panbio™ COVID-19 Ag Rapid Test Device (Abbott Diagnostics, Jena, Germany) for this purpose. Methods: A total of 634 individuals (355 female; median age, 37 years; range, 9–87) were enrolled. Two nasopharyngeal swabs were collected from household ( n = 338) and non-household contacts ( n = 296) of COVID-19 cases. RAD testing was carried out at the point of care. The RT-PCR test used was the TaqPath COVID-19 Combo Kit (Thermo Fisher Scientific, MA, USA). Results: Household contacts were tested at a median of 2 days (range, 1–7) after diagnosis of the index case, whereas non-household contacts ( n = 296) were tested at a median of 6 days (range, 1–7) after exposure. In total, 79 individuals (12.4%) tested positive by RT-PCR, of whom 38 (48.1%) yielded positive RAD results. The overall sensitivity and specificity of the RAD test was 48.1% (95% CI 37.4–58.9) and 100% (95% CI 99.3–100), respectively. Sensitivity was higher in household (50.8%; 95% CI 38.9–62.5) than in non-household (35.7%; 95% CI 16.3–61.2%) contacts. Individuals testing positive by RAD test were more likely (p < 0.001) to become symptomatic than their negative counterparts. Discussion: The Panbio test displays low sensitivity in asymptomatic close contacts of COVID-19 patients, particularly in non-household contacts. Nonetheless, establishing the optimal timing for upper respiratory tract collection in this group seems imperative to pinpoint test sensitivity.